2012
DOI: 10.1111/j.1439-0531.2012.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Ultrasonography in the Mare

Abstract: Ultrasonography has become indispensable in the control of equine reproduction. Mare ovary layers are inverted with respect to other species, with the follicles and corpus luteum found inside the ovary; only large follicles protrude from the organ's surface. This renders the making of diagnoses via rectal palpation of the ovaries very difficult. Ultrasound imaging, however, provides another avenue of examination. Since its first use in 1980, the diagnostic potential of ultrasonography has greatly improved. Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Both plasma progesterone levels and CL vascularization return to basal values 24 h after administration of prostaglandins. However, the size of the CL significantly decreases over the following 3 days (Miro, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Both plasma progesterone levels and CL vascularization return to basal values 24 h after administration of prostaglandins. However, the size of the CL significantly decreases over the following 3 days (Miro, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Monitoring follicular dynamics to predict the ovulation time for coordinating breeding or artificial insemination is one of the main clinical applications of ultrasound in routine reproductive practice (Ginther, 2007). The clinical signs of impending ovulation identified with B-mode ultrasound are a deformed preovulatory follicle, increased thickness and echogenicity of the granulosa, and a reduction of the prominence of the anechoic band peripheral to the granulosa band (Miro, 2012). Colour Doppler ultrasound has also been used to predict ovulation time.…”
Section: Follicular Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…While Gastal (15) we reported that ovulation about 10 percent occurs after the end of estrus in mares. The amount of endometrial edema in the uterine lumen is a declining day prior to ovulation; the edema development and regression are related to estrogen concentrations in estrus mares (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound monitoring of the follicular activity starts on the third day of estrus, and is performed daily on both ovaries with an ultrasound instrument (Aloka 500 ® ) provided with a 5 MHz linear probe. Ultrasound examination involves locating the preovulatory follicle in generally one of the two ovaries, and determining its diameter each time (Miro, 2012). As soon as the follicular diameter reaches 35 mm, the ultrasound examination becomes thrice a day (7am, 4pm and 11pm).…”
Section: Ovaries Ultrasoundmentioning
confidence: 99%